VALIDITAS PEWARNAAN TOLUIDINE BLUE SEBAGAI PETANDA ADANYA KARSINOMA SEL SKUAMOSA DI NASOFARINGS - , INAWATI BOBOT, DR.dr. Bambang Hariwiyanto, Sp.THT-KL(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Nasopharyngeal carcinoma is a squamous cell malignancy derived from epithel nasopharynx, commonly found in Southeast Asia and China. Nasopharyngeal carcinoma is the most common disease found in the ENT oncology clinic of Sardjito hospital and squamous cell carcinoma is the most than any other tumor histology. Biopsy is the gold standard examination for diagnosing nasopharyngeal carcinoma. Toluidine blue staining has been used more than 40 years to detect the presence of malignancy in the mucosa. This study use diagnostic test design, research subjects were all patients with suspected nasopharyngeal carcinoma who will perform a nasopharyngeal biopsy in accordance with inclusion criteria and exlusion criteria. Nasopharynx on study subjects stained with toluidine blue, then performed a biopsy with endoscopic guidance. Biopsi results examined in the pathological anatomy. Toluidine blue staining results true positive when appear blue color and the biopsi results are squamous cell carcinoma, toluidine blue staining results true negative when did not appear in blue and the biopsy results of the absence of squamous cell carcinoma. In this study the sensitivity of the toluidine blue staining for detection of squamous cell carcinoma in nasofarings was 86% and specificity was 67%. Obtained a positive predictive value of 86% and 67% negative predictive value. The positive likelyhood ratio in this research was 2.57 and the negative likelyhood ratio was 0.21. The conclusions in this study was toluidine blue could stained the tissue of squamous cell carcinoma compared to normal tissue so that it can be a marker of squamous cell carcinoma in nasofarings